SPECIALLY PROTECTED NATURAL AREAS OF LOCAL SIGNIFICANCE: PROBLEMS OF GOVERNANCE AND DEVELOPMENT - M. Stadolin; E. Yamchuk (Вестник университета)
The article analyzes the existing management system of specially protected natural areas of local significance, revealed current problems of their functioning and management at the municipal level, outlined alternative directions of further development of the local natural complexes and proposed arrangements for fuller use of natural-recreational potential of these territories.